2020
DOI: 10.48550/arxiv.2006.11289
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shadow cast by a rotating charged black hole in quintessential dark energy

Saeed Ullah Khan,
Jingli Ren

Abstract: The existence of quintessential dark energy around a black hole has considerable consequences on its spacetime geometry. Hence, in this article, we explore its effect on horizons and the silhouette generated by a Kerr-Newman black hole in quintessential dark energy. Moreover, to analyse the deflection angle of light, we utilize the Gauss-Bonnet theorem. The obtained result demonstrates that, due to the dragging effect, the black hole spin elongates its shadow in the direction of the rotational axis, while incr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…al [54]. Interestingly, effects of the cosmological constant are indistinguishable to the effect of quintessence parameter on BH's shadow presented in our earlier work [38]. We have also shown that at different inclination angles observer observes disparate shapes of the BH shadow.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…al [54]. Interestingly, effects of the cosmological constant are indistinguishable to the effect of quintessence parameter on BH's shadow presented in our earlier work [38]. We have also shown that at different inclination angles observer observes disparate shapes of the BH shadow.…”
Section: Discussionsupporting
confidence: 65%
“…As a result, the exploration of BH's shadow would be a rewarding technique to understand the astrophysical BHs and to compare the general theory of relativity with modern theories [37]. Khan and Ren [38] deduced that shadow radius increases with the increase of quintessence parameter, while the charge and spin parameters result in distortion of the BH shadow. The shadow of braneworld BH is investigated under the influence of the brane parameter [39].…”
Section: Introductionmentioning
confidence: 99%
“…A close inspection has revealed that DE affects also the optical aspect which has been dealt with using the shadow geometries in terms of one dimensional real curves. For certain black holes solutions, DE can be considered as a geometric deformation parameter controlling the size of the shadows [36,[45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…The first concept has been discussed in terms of one dimensional real curves [14][15][16][17]. In this way, the corresponding size and shape have been controlled by the involved black hole parameters [18][19][20][21][22]. The second notion concerns the deflection angle of light rays by black holes which has been investigated using different methods [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%